Correlation of cord blood glycated hemoglobin with macrosomia and neonatal hypoglycemia in infants born to diabetic mothers - Sujonitha John; Habeeb Ullah Khan; Jaidev Mangalore Devdas; Pavan Hegde (Wolters Kluwer Medknow Publications, 2020)
Background: Infants born to diabetic mothers are prone to hypoglycemia once transplacental supply of glucose is cut off due to which there is transient low blood glucose concentration during the first 2 h after delivery. Aim: Our study aimed at the correlation of cord blood glycated hemoglobin (HbA1c) with neonatal hypoglycemia and macrosomia in infants of diabetic mothers (IDMs). Methods: A descriptive longitudinal study was conducted on 100 consecutive IDMs with gestational age >34 weeks in a tertiary care hospital between November 2016 and December 2017, meeting the inclusion criteria. Infant and maternal details were recorded in a predesigned pro forma. Cord blood HbA1c in IDMs correlated with neonatal hypoglycemia and macrosomia. Results: Out of the 100 IDMs, 33 babies developed hypoglycemia. The mean cord blood HbA1c among hypoglycemic babies was 6.4% ± 0.9%, which was higher and statistically highly significant (P < 0.001) than babies who did not develop hypoglycemia. Most hypoglycemic events occurred at 30 min of postnatal life. The birth weight of IDMs correlated with cord blood HbA1c levels. Out of the 33 babies with hypoglycemia, 31 (94%) were macrosomic. Macrosomia increased the risk of hypoglycemia in IDMs (odds ratio: 78, 95% confidence interval: 16.4-379). Conclusion: Cord blood HbA1c showed a significant correlation with the risk of macrosomia and neonatal hypoglycemia.